Altered directed connectivity during processing of predictive stimuli in psychiatric patient populations. Issue 11 (November 2021) - Fogelson, Noa; Diaz-Brage, Pablo
Highlights: Schizophrenia and autism were associated with task-specific attenuation of top-down connectivity. Depression was associated with task-specific increases in top-down connectivity. Connectivity alterations observed during the processing of predictive stimuli. Abstract: Objectives: The study investigated the role of top-down versus bottom-up connectivity, during the processing of predictive information, in three different psychiatric disorders. Methods: Electroencephalography (EEG) was recorded during the performance of a task, which evaluates the ability to use predictive information in order to facilitate predictable versus random target detection. We evaluated EEG event-related directed connectivity, in patients with schizophrenia (SZ), major depressive disorder (MDD), and autism spectrum disorder (ASD), compared with healthy age-matched controls. Directed connectivity was evaluated using phase transfer entropy. Results: We showed that top-down frontal-parietal connectivity was weaker in SZ (theta and beta bands) and ASD (alpha band) compared to control subjects, during the processing of stimuli consisting of the predictive sequence. In SZ patients, top-down connectivity was also attenuated, during the processing of predictive targets in the beta frequency band. In contrast, compared with controls, MDD patients displayed an increased top-down flow of information, during the processing of predicted targets (alpha band). Conclusions: The findings suggest that top-down frontal-parietal connectivity is altered differentially across three major psychiatric disorders, specifically during the processing of predictive stimuli. Significance: Altered top-down connectivity may contribute to the specific prediction deficits observed in each of the patient populations.